Positioning system for sensor less linear DC motor - Misron, Norhisam; Mat Saad, Ezril Hashim; Raja Othman, Raja Nor Firdaus Kashfi; Abdul Shukor , Fairul Azhar; Wakiwaka, Hiroyuki; Nirei, Masami (2010)
Sensor less Linear DC Motor (LDM) positioning system is introduced to replace the expensive closed loop linear DC motor system. The system was operating in open loop condition. Spring displacement and variant of PWM’s duty cycle in certain time is used to achieve the LDM required displacement. The quadruple stage technique is used to improve the transient response of LDM. In this paper, sensor less positioning system for LDM had been proposed. The positioning expression and it performance had been studied.